Overexpressed Neuropilin-1 in Endothelial Cells Promotes Endothelial Permeability through Interaction with ANGPTL4 and VEGF in Kawasaki Disease - Junhua Huang; Shuwan Zhang (Hindawi Limited, 2021)
Disrupted endothelial permeability plays a crucial role in the vasculitis pathogenesis of Kawasaki disease (KD), which leads to pathological vascular leak and facilitates inflammatory cell infiltration in vascular lesions; however, the mechanisms involved in the development of endothelial barrier dysfunction during KD vasculitis are still largely unclear. Here, we found that sera from patients with KD can induce endothelial cell (EC) hyperpermeability compared to sera from healthy controls. We observed that serum vascular endothelial growth factor (VEGF) levels were increased in KD patients and sera from KD patients upregulated the expression of VEGF receptor 2 (VEGFR2) and neuropilin-1 (NRP1) in human coronary artery endothelial cells (HCAECs). Intriguingly, compared with silence of VEGFR2 in HCAECs, NRP1 silence resulted in a marked decrease in EC permeability. Furthermore, soluble NRP1 (sNRP1) remarkably reduced the stimulation of EC permeability by sera from KD patients compared with bevacizumab treatment. Importantly, we showed that besides VEGF, angiopoietin-like-4 (ANGPTL4), a NRP1-binding vasoactive factor, was also increased in KD and contributed to the EC permeability in KD conditions. In addition, levels of both ANGPTL4 and VEGF were inversely correlated with albumin levels in the serum of KD patients. Collectively, the data demonstrated that overexpressed NRP1, along with upregulated VEGFR2, in HCAECs treated with KD sera promotes endothelial permeability via interaction with the increased ANGPTL4 and VEGF in KD. Neutralization of hyperpermeability factors by sNRP1 may be a novel therapeutic strategy for KD vasculitis.